Formulation and Organoleptic Test on Cookies Made from Potato Peel Flour - Septiani, Septiani; Ratnayani, Ratnayani (Journal La Lifesci, 2025)
Processing potatoes into flour is one way to reduce the risk of damage and extend the shelf life of potatoes. Potato flour has high absorption, fine texture, sweet taste, and a distinctive fragrant aroma. Cookies are dry baked goods produced by baking dough made from wheat flour, either with or without substitutes, along with oil or fat, and optionally incorporating other food ingredients and approved additives. Based on this, it is necessary to conduct research on potato flour formulations in cookies with organoleptic tests to determine the best formulation for making cookies from potato peel flour, obtaining the best formulation it can reduce the dependence of the community and industry on the use of wheat flour. The research used a Completely Randomized Design (CRD) with four formulations (0%, 25%, 50%, and 75% potato peel flour substitution) and two repetitions. Organoleptic testing, including hedonic and hedonic quality assessments, was conducted to evaluate panellists' preferences for colour, texture, taste, and aroma. The results showed that cookies with 25% potato peel flour substitution (F1) were the most preferred, achieving the highest scores in all sensory attributes. However, increasing the substitution level resulted in a darker colour, firmer texture, and a more pronounced bitter taste, affecting overall acceptability.